Amino Acid Composition of Some New Varieties of Oil Seeds - Gupta, Manju; Shrivastava, S.K. (Asian Journal of Chemistry, 2010)
The amino acid composition of some new varieties of oil seeds (Arachis hypogaea JGN-3, Brassica campestris VARUNA, Carthamus tinctorius JSF-1, Glycine max JS-90-41 and Helianthus annus KBSH-1) were analyzed by high performance liquid chromatography.